Penerapan Model Pembelajaran Probing–Promting Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas ⅤII SMP Negeri 19 Tidore Kepulauan - Vella Totomo (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2023)
This study amis to improve the learning outcomes of in class VII SMP Negeri 19 Tidore through the Probing-Promting learning Model. The reseaech mothod used is quentitatif wher the research was conducted at SMP Negeri 19 Tidore Kepulauan class VII, whice totaled 24 studens. Data sources were from teacher and students. Reseaech data colletion techniques were carried out using observation sheet implementasi learning models and test question were analyzed descripitively quentitatif. Based on the researlts of research in class VII SMP Negeri 19 Tidore Kepulauan which was carried out with the results by students in cycle l showed thet there had been on increase using the Probing-Promting learning model on temperature and heat material the result was 50%. whereas in cycle II the learning outcoimes of students using the probing-promting learning model showed an incrase of 90% with an average volue of 80%.